Určení deformačně-napěťových stavů bimetalického prutu při změně teploty - Jurkovič, Vítězslav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2024)
Tato bakalářská práce se zabývá deformační a napěťovou analýzou zvoleného bimetalového pásku. Nejdříve je provedena rešerše používaných bimetalových pásků včetně uvedení používaných materiálů a kritérií k jejich výběru. Dále je proveden analytický výpočet volné deformace pásku při zvolené změně teploty pomocí prutových předpokladů. Následuje srovnání s výsledky získaných pomocí metody konečných prvků v systému Ansys Workbench. Analýza stejného pásku při omezení deformace je pak provedena pomocí metody konečných prvků. V té je nejdříve provedena analýza úplného zamezení deformace včetně verifikace výsledků pomocí náhrady deformační okrajové podmínky silovou. Následuje deformační analýza při omezení deformace zvolenou ventilovou pružinou včetně určení stlačení pružiny po vymezení vůle. Výstupy této práce jsou výsledky volné deformace pásku při dané změně teploty, analýza vznikajícího napětí v pásku vlivem zamezení deformace a výpočet stlačení ventilové pružiny při změně teploty bimetalového pásku.

This bachelor’s thesis deals with stress-strain analysis of a selected bimetallic strip. First, a literature search is carried out on used bimetallic strips, including introduction of used materials and criteria for their selection. Next, an analytical calculation of free deformation of the strip at the chosen temperature is performed using rod assumptions. The following is a comparison with the results obtained using finite element method in the Ansys Workbench system. The analysis of the same strip with limited deformation is then performed using the finite element method. In this way, a stress analysis of the complete deformation constraint is performed first, including verification of the results using substitute of the deformation boundary by a force one. The following is a deformation analysis when the deformation is constrained by the selected valve spring with existing clearance, including the determination of the compression of spring. The outputs of this thesis are the results of the free deformation of strip at given temperature change, the analysis of the resulting stresses in strip due to the constrained deformation and the calculation of compression of valve spring at temperature changes.
Evaluation of stress and deformation of a bimetallic beam under changed temperature
Keywords: Bimetalový pásek; deformačně-napěťová analýza; průhyb bimetalu; metoda konečných prvků; Ansys Workbench; Bimetallic strip; stress-strain analysis; bimetal deflection; finite element method; Ansys Workbench